Student-led strategies to counter bullying in inclusive schools for learners with special needs - Amjad Islam Amjad; Huda Alshamsi; Shamim Akhter; Kulaithem Al-khatri; Shaima Alyammahi; Sarfraz Aslam; Bisma Sajjad Sheikh; Nabil Saleh Sufyan; Abdulnaser Fakhrou (Environment and Social Psychology, 2025)
The literature supports that bullying is one of the significant psychological factors that hinder the successful implementation of inclusive education. The current study explores bullying interventions employed by special needs students in inclusive education settings in Pakistan. The study applied ecological systems, social learning, and social cognitive theories, highlighting the interplay of individual agency and socio-cultural context. The design of the present study was phenomenological. Twelve bullied students aged 12-16 participated in semi-structured interviews to identify strategies used to cope with and counter bullying. Thematic analysis revealed three main intervention approaches: peer support, self-advocacy, and avoidance. Findings illustrate the critical role of friendships, assertive communication, and withdrawal tactics. Family and teacher support, school environment, and prevailing social stigma significantly influenced students’ intervention efforts. The results highlight the need for culturally informed, holistic anti-bullying interventions empowering special needs students and strengthening peer networks. This research fills gaps in the Pakistani context and guides inclusive education policies and practices.